Ejercicios aeróbicos y su incidencia en el desarrollo de la resistencia de los estudiantes que practican futbol en la Unidad Educativa Clemente Baquerizo - Carrera Almache, Johanna Viviana (2017)
The research work is entitled: aerobic exercises and their impact on the development of the resistance of students who practice football in the Clemente Baquerizo educational unit. Which is within the Babahoyo Canton, Province of the Rivers Research is in the development of aerobic capacities. The information contained in the data of the students' information and that of the information about the education and the use of an information for the handling of the information and execution. The final report was framed in the type of descriptive research. A series of techniques and devices for data collection, direct observation, brochures, ICTs were used to support education. For the elaboration of the report I realize the objectives, the statistical analysis of the obtained data, being able to establish the conclusions and recommendations. In this way it was possible to conclude with the elaboration of a proposal of a methodological guide of aerobic exercises to achieve a great impact in the development of the resistance for the institution in which this research was carried out